2015
DOI: 10.1098/rspb.2014.2688
|View full text |Cite
|
Sign up to set email alerts
|

Variation inDrosophila melanogastercentral metabolic genes appears driven by natural selection both within and between populations

Abstract: In this report, we examine the hypothesis that the drivers of latitudinal selection observed in the eastern US Drosophila melanogaster populations are reiterated within seasons in a temperate orchard population in Pennsylvania, USA. Specifically, we ask whether alleles that are apparently favoured in northern populations are also favoured early in the spring, and decrease in frequency from the spring to autumn with the population expansion. We use SNP data collected for 46 metabolic genes and 128 SNPs represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…One study has found season-dependent oscillating patterns of allele frequency change of central metabolic and nutrient sensing genes (Cogni et al, 2015). than all previous studies (~42%: yeast extract) and thus our study is more informative about the effects of protein on dietary preference.…”
Section: Discussionmentioning
confidence: 57%
“…One study has found season-dependent oscillating patterns of allele frequency change of central metabolic and nutrient sensing genes (Cogni et al, 2015). than all previous studies (~42%: yeast extract) and thus our study is more informative about the effects of protein on dietary preference.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, these activity differences are representative of the range of much of the cis-associated SNP expression variation seen in natural populations [34,38]. The observation that metabolic genes, when perturbed modestly in activity, have an effect on lifespan is certainly relevant to discussions of the maintenance of genetic variation in these genes in natural populations, especially as nutrient levels vary geographically and seasonally [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In D. melanogaster, the genes of the central metabolic pathway harbour considerable sequence and expression variation [34][35][36], which often shows change with latitude and season [37][38][39]. In this regard, unlike the other experimental models used in aging studies, Drosophila offers the unique opportunity to associate aging and signalling pathways with their population genetics [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Populations of flies living in orchards evolve over the period of months (Bergland, Behrman, O'Brien, Schmidt, & Petrov, 2014) as they track changing fitness optima influenced by seasonal fluctuations in selection pressure (Machado et al, 2018). Although many life-history and stress tolerance traits have been shown to exhibit adaptive tracking across short timescales (e.g., Behrman et al, 2018;Behrman et al, 2015;Cogni et al, 2014Cogni et al, , 2015, some of these traits are also highly plastic (e.g., Ayrinhac et al, 2004;Chippindale, Leroi, Kim, & Rose, 2004).…”
Section: Introductionmentioning
confidence: 99%